Seznam jetrenjakov (Marchantiophyta) in rogovnjakov (Anthocerotophyta) Slovenije - Martinčič, Andrej (Scopolia, 2011)
The list of liverworts (Marchantiophyta) and hornworts (Anthocerotophyta) of Slovenia within current political boundaries comprises 166 species, 2 subspecies and 9 most common varieties. Additional 5 species are denoted by a question mark since these reports are considered questionable for whatever reason. An alphabetically arranged tabular presentation of genera and species,as well as lower taxa, also shows their presence in individual phytogeographical units of Slovenia. Corresponding symbols present records from the period before and after 1960. The Checklist includes the data taken from the literature and LJU herbarium. Annotations give a critical evaluation of special literature and herbarium data. A list of species that should be excluded from the flora of Slovenia, and the synonyms used in the floristic literature for Slovenia have been added. A short review of liverworts - hornworts research in Slovenia and a list of literature with floristic data for Slovenia are also included.
Keywords: Rhododendron-Park Bremen; botanika; jetrenjaki; rogovnjaki; seznami; Slovenia; Slovenija